2008
DOI: 10.1118/1.2962345
|View full text |Cite
|
Sign up to set email alerts
|

MO-D-AUD B-04: Parameter Optimization for Brachytherapy Robotic Needle Insertion and Seed Deposition

Abstract: Purpose: To investigate influence of different needle insertion and seed deposition techniques for robotic brachytherapy. To find optimal sets of low, normal and high translational and rotational velocities of the needle for decreasing insertion force, needle deflection and OR time, and increasing seed placement accuracy. Method and Materials: We have developed EUCLIDIAN — a fully automatic robotic prostate brachytherapy system. Robotic system parameters were optimized via preclinical experiments using two typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Influence of the external contact forces is described by factor f . Combining (13)- (17) the mathematical model of the system is…”
Section: Mathematical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Influence of the external contact forces is described by factor f . Combining (13)- (17) the mathematical model of the system is…”
Section: Mathematical Frameworkmentioning
confidence: 99%
“…Generally, to improve needle placement and seed deposition in brachytherapy procedure several methods have been presented in the literature, such as parameter optimization, different needle rotation techniques, robotic insertion, force modeling, and needle steering techniques. In the previous studies, we concluded that the proper selection of the translational and rotational velocities may reduce tissue deformation and target movements by reducing insertion force [17][18][19]. Therefore, it can be concluded that the insertion force has a dominant influence on the needle insertion, seed deposition precision, and dosimetry distribution in brachytherapy procedure.…”
Section: Introductionmentioning
confidence: 99%
“…These insertion forces are significantly responsible for needle deviation from the desired trajectory and target movement. Proper selection of the translational and rotational velocities may reduce the tissue deformation and target movement by reducing insertion force, [5]- [7]. In the current study, we used a neural network predictive controller to predict insertion force in order to achieve real- time adaptive needle control.…”
Section: Introductionmentioning
confidence: 99%